LIFETIME SEXUAL AND PHYSICAL ABUSE AMONG ELITE ATHLETIC ATHLETES: A CROSS-SECTIONAL STUDY OF PREVALENCE AND CORRELATES WITH ATHLETICS INJURY. Issue 7 (11th March 2014) - Timpka, T; Janson, S; Jacobsson, J; Kowalski, J; Ekberg, J; Mountjoy, M; Svedin, CG
Abstract : Background: Sexual and physical abuse have been reported from all levels of sports. Associations between abuse victimization and sports injury have not been fully investigated. Objective: To examine the lifetime prevalence of sexual and physical abuse in elite athletics athletes and explore associations with prevalence of athletics injuries. Design: Cross-sectional study using e-epidemiological survey methods. Setting: Swedish male and female youth and adult elite athletics athletes. Participants: Athletes ranked in the national top-15 with recorded email addresses (n=507) were invited. 198 (39%) athletes returned complete data. Risk factor assessment: Gender, age, sexual orientation, event group, lifetime physical abuse, lifetime sexual abuse (noncontact sexual abuse (indecent exposure), contact sexual abuse without penetration, penetrating sexual abuse) within and outside sports. Main outcome measurements: One-year prevalence of injury causing at least three consecutive weeks of full or partial time loss from athletics. Results: 27 (14%) athletes reported lifetime exposure to sexual abuse and 36 (18%) athletes to physical abuse. More women than men (P=.005; Cramer's V=0.21) reported lifetime sexual abuse. Non-heterosexual athletes tended to more often be lifetime physical abuse victims than their heterosexual peers (P=.058). 6 (3%) athletes reported having been sexually abused in the athletics setting. The perpetrators of sexual abuse in athletics were both men and women extending from coaches to peers in mid-adolescence; two athletes reported suicidal ideation as a consequence of the abuse. The one-year prevalence of 3-week athletics injuries was higher for physical abuse victims among women (P=.021; Cramer's V=0.23), but not for male victims (P=.90). Sexual abuse was not found to be statistically associated with athletics injury. Conclusions: Physical abuse victimization was associated with higher injury prevalence among female athletics athletes. Sexual and physical abuse victims are common in elite athletics and further studies of abuse, abuse victims, and abuse prevention are needed.